Comprehensive metabolomic and lipidomic alterations in response to heat stress during seed germination and seedling growth of Arabidopsis - Qian, Wenjuan; Zhu, Yuxuan; Chen, Qinsheng; Wang, Shuaiyao; Chen, Longlong; Liu, Ting; Tang, Huiru; Yao, Hongyan (Frontiers in Plant Science, 2023)
Temperature affects seed germination and seedling growth, which is a critical and complex stage in plant life cycle. However, comprehensive metabolic basis on temperature implicating seed germination and seedling growth remains less known. Here, we applied the high-throughput untargeted metabolomic and advanced shotgun lipidomic approaches to profile the Arabidopsis 182 metabolites and 149 lipids under moderate (22℃, 28℃) and extreme high (34℃, 40℃) temperatures. Our results showed that a typical feature of the metabolism related to organic acids/derivates and amines was obviously enriched at the moderate temperature, which was implicated in many cellular responses towards tricarboxylic acid cycle (TCA), carbohydrates and amino acids metabolism, peptide biosynthesis, phenylpropanoid biosynthesis and indole 3-acetate (IAA) biosynthetic pathway. Whereas, under extreme high temperatures, there was no seed germination, but 148 out of total 182 metabolites were highly enriched, involving in the galactose metabolism, fatty acid degradation, tryptophan/ phenylalanine metabolism, and shikimic acid-mediated pathways especially including alkaloids metabolism and glucosinolate/flavone/flavonol biosynthesis. Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) also exhibited the gradually increased tendency from moderate temperatures to extreme high temperatures; whereas phosphatidylserine (PS), phosphatidic acid (PA), phosphatidylglycerol (PG), monogalactosyldiacylglycerol (MGDG), digalactosyldiacylglycerol (DGDG) and sulfoquinovosyldiacylglycerol (SQDG) were contrary to decrease. Another typical feature of the distinguished metabolites between 22℃ and 28℃, the TCA, disaccharides, nucleotides, polypeptides, SQDG and the biosynthesis of fatty acids and glucobrassicin-mediated IAA were obviously decreased at 28℃, while amino acids, trisaccharides, PE, PC, PA, PS, MGDG, DGDG and diacylglycerol (DAG) preferred to enrich at 28℃, which characterized the alteration of metabolites and lipids during fast seedling growth. Taking together, our results provided the comprehensive metabolites phenotyping, revealed the characteristics of metabolites necessary for seed germination and/or seedling growth under different temperatures, and provided insights into the different metabolic regulation of metabolites and lipid homeostasis for seed germination and seedling growth.